Evaluation of dithiothreitol-oxidizing capacity (DOC) as a serum biomarker for chronic hepatitis B in patients exhibiting normal alanine aminotransferase levels: a pilot study towards better monitoring of disease. (December 2021) - Yang, Lumin; Zhang, Yafei; Zhang, Ke; Liu, Zhongping; He, Tengfei; Zheng, Xiaowei; Li, Lei; Arnér, Elias S J; Zhang, Zhenhua; Zhang, Jinsong
Abstract: Background: Alanine aminotransferase (ALT) is the most commonly used serum biomarker for chronic liver diseases (CLDs) but may not accurately reflect hepatic disorders and easily underestimates hepatic fibrosis. The previously revised upper limit of normal (ULN) of ALT (19 U/L for women and 30 U/L for men) increases its sensitivity but yields higher numbers of false-positives. Moreover, CLDs patients with ALT lower than the revised ULN may nonetheless have progression of disease. Therefore there is a need of novel biomarkers to complement the use of ALT. Here we have evaluated measurements of serum d ithiothreitol-o xidizing c apacity (DOC) in cohorts of chronic hepatitis B patients with different stages of disease as an exploratory pilot study for this purpose. Methods: Serum samples obtained from healthy persons and from chronic hepatitis B patients with normal ALT values were used for sensitivity evaluation. The hepatitis B patients encompassed end-stage liver diseases (ELD), chronic hepatitis B (CHB), CHB with persistently normal ALT (CHB-P) and inactive carriers (ICs). Sensitivity was also evaluated with samples from patients with other diseases. The study period was March 2018 to December 2020. Findings: DOC was found to be a robust biomarker that may become complementary to ALT measurements, especially in patients displaying low ALT levels. ROC analyses indicated that the AUC values of DOC reached 0.983 and 0.956 in ELD and CHB patients exhibiting normal ALT levels, respectively. Importantly, the AUC values of DOC reached 0.852 and 0.844 in CHB-P patients and ICs, respectively. Such AUC values permit screening and continued monitoring, corresponding to over 30% and 50% sensitivity with 99% and 95% specificity for CHB-P and ICs, respectively. DOC was also significantly correlated with indicators for fibrosis, assessing both APRI (Pearson r = 0.4905, P < 0.0001) and FIB-4 (Pearson r = 0.4421, P < 0.0001). Surprisingly, the AUC values of DOC in the hepatitis B patients with ALT levels lower than the revised ULN were not compromised. In examined non-liver diseases, DOC was low and normal, including in patients with acute myocardial infection displaying increased ALT levels. Interpretations: The results suggest that DOC can be promising as a complementary biomarker used in addition to ALT for monitoring of disease in chronic hepatitis B patients, especially when ALT levels are normal. DOC should be further evaluated for possible clinical use as biomarker also in other CLDs. Funding: This study was funded by the National Natural Science Foundation of China (Grant numbers: 31771971 and 32001013).